Negligently caused pure economic loss from a comparative perspective - Von Bodenhausen, Eckard Freiherr (Centre for Law and Society, 2024)
The problem of pure economic loss, which refers to financial loss that is not the result of physical damage to the person or property of the plaintiff, 1 has a long history and is still controversial in many systems. In a nwnber of legal systems, compensation for pure economic loss is not allowed,2 however, the jurisprudence and courts of these systems have tried to develop mechanisms to cover such loss in certain instances.3 This dissertation looks at the problem of negligently caused pure economic loss from a comparative perspective. A comparison is made between the legal system of English and Germany. The German and English law differ in so far as English law is a common law and the German is a code law. Both countries have developed different approaches to solve the problem of pure economic loss; in England, the law of tort was expanded and in Germany, the law of contract was expanded. This paper demonstrates, however, that both systems arrive at the same general result. This dissertation focuses only on the ncm-cqntractual liability for negligently caused pure economic loss. Liability for fatal accidents will not be included. The first chapter presents the English approach in the field of negligently caused pure economic loss in accordance with landmark decisions. The second chapter deals with the German approach. The emphasis of this chapter lies on the expansion of the law of contract.